2020
DOI: 10.21203/rs.2.23829/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

E-cigarette-Induced Pulmonary Inflammation and Dysregulated Repair are Mediated by nAChR α7 Receptor

Abstract: Electronic cigarette (e-cig) vaping is increasing rapidly in the United States, as e-cigs are considered less harmful than combustible cigarettes. However, limited research has conducted to understand the mechanism of toxicological and pulmonary effects of e-cigs. We hypothesized that sub-chronic exposure of e-cigs induced inflammatory response and dysregulated repair/extracellular matrix (ECM) remodeling, which occur through the α7 nicotinic acetylcholine receptor (nAChR α7). Adult wild-type (WT), nAChRα7 kno… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…When people smoke, nicotine induces overexpression of the ACE2 receptor in pulmonary epithelial cells (e.g., bronchial epithelial cells, type II alveolar epithelial cells.) through nAChRα7 (Biron et al, 1969;Wang Q. et al, 2020), and studies have confirmed that smokers (including e-cigarettes) have higher serum levels of ACE-2 in Figure 2 (Brake et al, 2020). In healthy human volunteers, serum ACE activity increased significantly immediately after smoking and returned to control levels 20 min after smoking cessation (Kitamura, 1987).…”
Section: Nicotine Affects Ace2 Expression Increases Susceptibility Tmentioning
confidence: 91%
See 1 more Smart Citation
“…When people smoke, nicotine induces overexpression of the ACE2 receptor in pulmonary epithelial cells (e.g., bronchial epithelial cells, type II alveolar epithelial cells.) through nAChRα7 (Biron et al, 1969;Wang Q. et al, 2020), and studies have confirmed that smokers (including e-cigarettes) have higher serum levels of ACE-2 in Figure 2 (Brake et al, 2020). In healthy human volunteers, serum ACE activity increased significantly immediately after smoking and returned to control levels 20 min after smoking cessation (Kitamura, 1987).…”
Section: Nicotine Affects Ace2 Expression Increases Susceptibility Tmentioning
confidence: 91%
“…Buscetta et al (2020) found that cigarette smoke extract could increase the activity of caspase-1 through an NLRP3-independent and TLR4-TRIFcaspase-8-dependent pathway, leading to a decrease in basic glycolytic flux and response to lipopolysaccharide, which may eventually lead to macrophage dysfunction and increase the risk of infection in smokers. Simultaneously, in the context of subchronic electronic cigarette exposure, the body increases the release of pro-inflammatory factors and ACE2 receptors by regulating nAChRα7, leading to an inflammatory response and dysregulated repair (Wang Q. et al, 2020). The De Cunto team (De Cunto et al, 2016) showed that, under chronic smoking conditions, the expression of some pro-inflammatory cytokines was upregulated (e.g., Il-6, TNF-α, KC).…”
Section: Nicotine Il-6 and Other Pro-inflammatory Factorsmentioning
confidence: 99%
“…The ratio of AT 1 R to AT 2 R increased five to six fold in bronchiole areas with enhanced fibrosis, which were associated with diminished lung function in COPD patients (Bullock et al, 2001). A recent study also showed that sub-chronic e-Cig exposure enhances lung inflammation and ACE2 expression which were shown to be mediated by α7 nAChRs (Wang et al, 2020c disorders in association with COVID-19 infection (Maremanda et al, 2020). These results indicate that smokers and/or vapers may have an increased risk of COVID-19 related complications which can aggravate disease severity and treatment outcome.…”
Section: Lungmentioning
confidence: 93%
“…nAChRs (Wang et al, 2020c). Further studies are definitely warranted to determine the effects of nicotine on inflammation.…”
Section: Lungmentioning
confidence: 99%
“…Interestingly, a recent population-study, that surveyed 4351 adolescents and young adults aged 13-24 years, highlighted that the effects of vaping may collide with the risk of COVID-19, thus users are at a five--seven-times increased risk of a COVID-19 diagnosis, compared with non-users (data adjusted for major confounders, such as age, sex, and obesity [63]. It has been recently hypothesized that sub-chronic e-cig exposure induces inflammatory response and dysregulated repair/extracellular matrix (ECM) remodeling, which occur through the α7 nicotinic acetylcholine receptor (nAChR α7) [64]. On the other hand, Changeux et al [65] advanced the hypothesis that SARS-CoV-2 may enter the body through neurons of the olfactory system and/or through the lung, and no through ACE2.…”
Section: Physical Characteristicsmentioning
confidence: 99%